Association between Neuroimaging Scores and Clinical Status in Pediatric Patients Diagnosed with Metachromatic Leukodystrophy - Sunho Lee; Ji Hoon Na; Young-Mock Lee (Annals of Child Neurology)
Purpose Metachromatic leukodystrophy (MLD) is a lysosomal storage disease caused by arylsulfatase A deficiency, which leads to progressive demyelination in both the central and peripheral nervous systems, resulting in significant gross motor deterioration. This study aimed to analyze data concerning neuroimaging and clinical phenotypes of MLD patients, categorized by disease subtype. Methods Patients diagnosed with MLD based on arylsulfatase A enzymatic activity, demyelination observed in brain magnetic resonance images, and/or pathogenic mutations were included in this study. The medical charts of 10 patients with confirmed MLD were retrospectively reviewed. We used a simplified magnetic resonance imaging (MRI) scoring system and clinical status, including survival. We analyzed the correlations between the scores of specific neuroimaging lesions and clinical status in two groups, categorized as late-infantile and juvenile types based on the age at symptom onset. Results We detected a positive relationship between clinical function deterioration and MRI score (rho=0.59, P=0.002) in patients with MLD. This correlation was stronger in the late-infantile type (rho=0.700, P=0.003) than in the juvenile type (rho=0.513, P=0.029). A strong relationship was also noted in patients with high signal intensities in the pons and basal ganglia, and cerebellar atrophy, but not in those with lesions in the midbrain. MLD with a high MRI score was associated with poor clinical function. Conclusion The identified correlations between modified MRI scores and clinical function scales may help predict the prognosis of patients with MLD, thereby aiding in the identification of treatment options and enhancing the quality of life for these patients.